5-Aminolevulinic Acid (ALA) Alleviated Salinity Stress in Cucumber Seedlings by Enhancing Chlorophyll Synthesis Pathway - Yue Wu; Xin Jin; Weibiao Liao; Linli Hu; Mohammed M. Dawuda; Mohammed M. Dawuda; Xingjie Zhao; Zhongqi Tang; Tingyu Gong; Jihua Yu (Frontiers in Plant Science, 2018)
5-Aminolevulinic acid (ALA) is a common precursor of tetrapyrroles as well as a crucial growth regulator in higher plants. ALA has been proven to be effective in improving photosynthesis and alleviating the adverse effects of various abiotic stresses in higher plants. However, little is known about the mechanism of ALA in ameliorating the photosynthesis of plant under abiotic stress. In this paper, we studied the effects of exogenous ALA on salinity-induced damages of photosynthesis in cucumber (Cucumis sativus L.) seedlings. We found that the morphology (plant height, leave area), light utilization capacity of PS II [qL, Y(II)] and gas exchange capacity (Pn, gs, Ci, and Tr) were significantly retarded under NaCl stress, but these parameters were all recovered by the foliar application of 25 mg L-1 ALA. Besides, salinity caused heme accumulation and up-regulation of gene expression of ferrochelatase (HEMH) with suppression of other genes involved in chlorophyll synthesis pathway. Exogenously application of ALA under salinity down-regulated the heme content and HEMH expression, but increased the gene expression levels of glutamyl-tRNA reductase (HEMA1), Mg-chelatase (CHLH), and protochlorophyllide oxidoreductase (POR). Moreover, the contents of intermediates involved in chlorophyll branch were increased by ALA, including protoporphyrin IX (Proto IX), Mg-protoporphyrin IX (Mg-Proto IX, protochlorophyllide (Pchlide), and chlorophyll (Chl a and Chl b) under salt stress. Ultrastructural observation of mesophyll cell showed that the damages of photosynthetic apparatus under salinity were fixed by ALA. Collectively, the chlorophyll biosynthesis pathway was enhanced by exogenous ALA to improve the tolerance of cucumber under salinity.